Warum Vorschulkinder nicht zurückgrüssen müssen. Beobachtungen zu Spezifika des kindlichen Sequenzmusters in der Grusshandlung - Schaad, Katrin; Zollinger, Esther (Linguistik Online, 2008)
The pilot study takes into focus a so far widely unexamined branch of language acquisition and developmental psychology. The object of investigation is the salutatory behavior of children between four and seven years of age. The analysis of data gathered in a Swiss kindergarten allows deriving a pattern of sequences for the preschooler's salutatory habits. Children tend to remain passive during greeting episodes or perform fragmentary salutations: They follow their own rituals of greeting. The childish salutatory behavior differs from the conventionalized norms valid for adults. This divergence, which is often considered deficient and reduced to a lack of politeness on the child's part, is in fact a normal state in the process of socialization A notable difference between the four- and the seven-year-olds has been observed: The older the children are, the more do their greetings correspond to the salutatory rituals conventionalized in society. This allows the conclusion that greeting behavior is not acquired simultaneously with language – preschoolers have already acquired language to a large extent, while they are still in midst of the process of socialization.